A phase 2 trial of the GSK‐3 inhibitor tideglusib in progressive supranuclear palsy. Issue 4 (14th February 2014) - Tolosa, Eduardo; Litvan, Irene; Höglinger, Günter U.; Burn, David; Lees, Andrew; Andrés, María V.; Gómez‐Carrillo, Belén; León, Teresa; del, Teodoro; ,
ABSTRACT It is believed that glycogen synthase kinase‐3 (GSK‐3) hyperphosphorylates tau protein in progressive supranuclear palsy (PSP). The Tau Restoration on PSP (TAUROS) study was a double‐blind, placebo‐controlled, randomized trial to assess the efficacy, safety, and tolerability of tideglusib, a GSK‐3 inhibitor, as potential treatment for PSP. The study enrolled 146 PSP patients with mild‐to‐moderate disease who were randomized to receive once‐daily 600 mg tideglusib, 800 mg tideglusib, or placebo (ratio, 2:2:1) administered orally over 52 weeks. The primary endpoint was the change from baseline to week 52 on the PSP rating scale. Secondary endpoints were safety and tolerability of tideglusib, changes in motor function (the Timed Up and Go Test), cognition (Dementia Rating Scale‐2, Frontal Assessment Battery, verbal fluency), apathy (Starkstein scale), activities of daily living (Schwab and England scale; Unified Parkinson's Disease Rating Scale, part II), quality of life (EuroQol), and Global Clinical Assessment. Brain atrophy on magnetic resonance imaging and several biomarkers in plasma and cerebrospinal fluid also were examined. No significant differences were detected in the primary or secondary endpoints at week 52 between placebo and either dose of tideglusib. Tideglusib was safe, with the exception of some asymptomatic, transient, and reversible transaminase elevations (mainly alanine aminotransferase) in 9% of patients, and diarrhea in 13% of patients. Tideglusib was generally well tolerated but it did not show clinical efficacy in patients with mild‐to‐moderate PSP. © 2014 International Parkinson and Movement Disorder Society